RANCANGAN ALAT PENGUKUR SUHU KELEMBABAN TANAH SEBAGAI ALAT BANTU PENENTU BENIH SAYURAN YANG AKAN DIBUDIDAYAKAN - Nursita, Putri; Anugreni, Fera; Khairuman, Khairuman; Candra, Rudi Arif; Fardiansyah, Fardiansyah (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
Vegetables are food ingredients that are very high in nutritional content. Good vegetables are vegetables that grow optimally which are influenced by several factors, one of which is the temperature of the soil moisture and optimal growth of vegetable seeds must be planted in a place suitable for vegetable seeds. A soil moisture temperature measuring device was designed to help determine the vegetable seeds that will be planted in a place. The tool is designed using a Capacitive Soil Moisture sensor and a 16x2 LCD Display is used to display the name of the seed and soil moisture. From the results of the measurement data, it is known how much the soil moisture temperature is in the measured place so that it can help in determining the vegetable seeds to be planted.